(4x-5)(3-2x)=12-9(2x-5)

Simple and best practice solution for (4x-5)(3-2x)=12-9(2x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x-5)(3-2x)=12-9(2x-5) equation:


Simplifying
(4x + -5)(3 + -2x) = 12 + -9(2x + -5)

Reorder the terms:
(-5 + 4x)(3 + -2x) = 12 + -9(2x + -5)

Multiply (-5 + 4x) * (3 + -2x)
(-5(3 + -2x) + 4x * (3 + -2x)) = 12 + -9(2x + -5)
((3 * -5 + -2x * -5) + 4x * (3 + -2x)) = 12 + -9(2x + -5)
((-15 + 10x) + 4x * (3 + -2x)) = 12 + -9(2x + -5)
(-15 + 10x + (3 * 4x + -2x * 4x)) = 12 + -9(2x + -5)
(-15 + 10x + (12x + -8x2)) = 12 + -9(2x + -5)

Combine like terms: 10x + 12x = 22x
(-15 + 22x + -8x2) = 12 + -9(2x + -5)

Reorder the terms:
-15 + 22x + -8x2 = 12 + -9(-5 + 2x)
-15 + 22x + -8x2 = 12 + (-5 * -9 + 2x * -9)
-15 + 22x + -8x2 = 12 + (45 + -18x)

Combine like terms: 12 + 45 = 57
-15 + 22x + -8x2 = 57 + -18x

Solving
-15 + 22x + -8x2 = 57 + -18x

Solving for variable 'x'.

Reorder the terms:
-15 + -57 + 22x + 18x + -8x2 = 57 + -18x + -57 + 18x

Combine like terms: -15 + -57 = -72
-72 + 22x + 18x + -8x2 = 57 + -18x + -57 + 18x

Combine like terms: 22x + 18x = 40x
-72 + 40x + -8x2 = 57 + -18x + -57 + 18x

Reorder the terms:
-72 + 40x + -8x2 = 57 + -57 + -18x + 18x

Combine like terms: 57 + -57 = 0
-72 + 40x + -8x2 = 0 + -18x + 18x
-72 + 40x + -8x2 = -18x + 18x

Combine like terms: -18x + 18x = 0
-72 + 40x + -8x2 = 0

Factor out the Greatest Common Factor (GCF), '8'.
8(-9 + 5x + -1x2) = 0

Ignore the factor 8.

Subproblem 1

Set the factor '(-9 + 5x + -1x2)' equal to zero and attempt to solve: Simplifying -9 + 5x + -1x2 = 0 Solving -9 + 5x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. 9 + -5x + x2 = 0 Move the constant term to the right: Add '-9' to each side of the equation. 9 + -5x + -9 + x2 = 0 + -9 Reorder the terms: 9 + -9 + -5x + x2 = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -5x + x2 = 0 + -9 -5x + x2 = 0 + -9 Combine like terms: 0 + -9 = -9 -5x + x2 = -9 The x term is -5x. Take half its coefficient (-2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. -5x + 6.25 + x2 = -9 + 6.25 Reorder the terms: 6.25 + -5x + x2 = -9 + 6.25 Combine like terms: -9 + 6.25 = -2.75 6.25 + -5x + x2 = -2.75 Factor a perfect square on the left side: (x + -2.5)(x + -2.5) = -2.75 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 9+2+4=183652 | | 3(5x+6x)=108 | | 4x-72=-36 | | 4(x-14)=160 | | 4t+20-15= | | y=-4x^2+2x-3 | | 0=x^2+20x+208 | | 0=x^2+20+208 | | 40=2x+5+2x-3 | | tanx=0.5714 | | 3x+5(6.5)=37 | | 7(5y-4)=21y | | er^10=2er^1 | | x+3+2(x-4)=28 | | 14n^2+14n=0 | | 0.25x+3.5=20 | | 2k+6=11 | | 0.25x+3.5=0 | | 3(-y+8)+5y=37 | | 3(3+5m)-12+(-3m)= | | 4b-2+7b=20 | | 19-(x+8)=6x+3 | | -4y/4= | | 2(5)-3y=9 | | 2x-3y=y | | 2x-3y=p | | 30=-16t^2+130t+90 | | 3x+22+2x+88=60 | | 3-5f-7-3f=9 | | 7x+1y+2z=46 | | 3p(p+5)4(p-7)= | | 2x+88+3x+22=60 |

Equations solver categories